2001
DOI: 10.1051/apido:2001137
|View full text |Cite
|
Sign up to set email alerts
|

The antifungal action of three South African honeys on Candida albicans

Abstract: -The purpose of this study was to investigate the antifungal action of three single samples of South African honey (wasbessie, bluegum and fynbos) against Candida albicans. Various dilutions of honey were prepared in brain-heart infusion broth, ranging in concentration from 0 to 25% (w/w). This was inoculated with C. albicans, while a hypertonic sugar solution served as a control. All dilutions were incubated overnight and the optical density was measured in a spectrophotometer. The sugar control and the 3 hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 18 publications
2
29
0
1
Order By: Relevance
“…This was observed in all microorganisms tested (Table 2). In the same way, previous reports demonstrated that increased honey concentrations resulted in reduced growth of C. albicans, namely 29.4% inhibition on the growth was verified in the presence of wasbessie honey at concentrations of 25% (Theunissen et al 2001). The minimum inhibitory concentration of honeys against isolates of Candida species (C. albicans C. glabrata and C. dubliniensis) would be achievable in a clinical setting (Irish et al 2006); C. dublinensis was more susceptible to the osmotic effect of all honeys, and to the antifungal effects of Jarrah honey.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This was observed in all microorganisms tested (Table 2). In the same way, previous reports demonstrated that increased honey concentrations resulted in reduced growth of C. albicans, namely 29.4% inhibition on the growth was verified in the presence of wasbessie honey at concentrations of 25% (Theunissen et al 2001). The minimum inhibitory concentration of honeys against isolates of Candida species (C. albicans C. glabrata and C. dubliniensis) would be achievable in a clinical setting (Irish et al 2006); C. dublinensis was more susceptible to the osmotic effect of all honeys, and to the antifungal effects of Jarrah honey.…”
Section: Introductionsupporting
confidence: 74%
“…To date, very few attempts have been made to assess the antifungical properties of honey (Theunissen et al 2001;Irish et al 2006;Küçük et al 2007;Boukraa et al 2008;Koc et al 2008), especially as compared to the large volume of published literature which has established that honey has significant antibacterial activity. The incidence of fungal infections is increasing in community and hospital environments (Fridkin 2005) and no other mycotic patho-gen produces as great a spectrum of opportunistic diseases in humans and animals as Candida does (Pappas et al 2003;Tortorano et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing and studying the therapeutic properties of honeys, modern science has made it possible to specify their medical significance for healing wounds and burns (Molan, 2001), oncology care (Bardy et al, 2008), as well as its antioxidant and antimicrobial factors (Gomes et al, 2010;Akbulut et al, 2009;Theunissen et al, 2001). It is clear that honeys to be used for therapeutic purposes should be harvested in areas with no contamination sources (Feás and Estevinho, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the face of the persistent honey-induced hyperglycemia, the body weight of these patients decreased without diet restrictions, and they did not develop DKA or HHS. The antioxidant [12][13][14], the anti-microbial [15][16][17][18][19], the immune modulator [20] and the anti-inflammatory properties [21][22][23][24] of honey helps also justification for this research.…”
Section: Justification Of the Researchmentioning
confidence: 99%
“…Moreover, honey is not expensive. Honey as an emerging novel anti-diabetic agent has been recently recognized in several studies [5][6][7][8][9][10][11], suggesting that honey, through its anti-oxidant [12][13][14], anti-microbial [15][16][17][18][19], immune modulator [20] and anti-In November, 2013, author reported in the journal of clinical trials a case of Coronary Heart Disease (CHD), hypertension and type 2 DM, who stopped his medicines and used honey as an alternative therapy for almost 11 years [25]. In spite of persistent hyperglycemia and dyslipidemia, unexpectedly, his blood pressure was controlled, his CHD improved or at least stabilized.…”
Section: Introductionmentioning
confidence: 99%